Removability of an Isolated Singularity of Solutions of Nonlinear Elliptic Equations with Absorption - Skrypnik, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We prove a priori estimates for singular solutions of nonlinear elliptic equations with absorption. Using these estimates, we establish precise conditions for the behavior of the absorption term of the equation under which solutions with point singularities do not exist.